Factors influencing macrophage phagocytosis and killing of Gram negative bacteria - Kurzyp, K (2024)
Gram negative infections pose a significant burden on human health. Escherichia coli causes blood stream infection and sepsis, while Neisseria gonorrhoeae is a leading causes of pelvic inflammatory disease, infertility and ectopic pregnancy. New ways to understand immune evasion and to target these bacteria are needed. My work aimed to investigate the mechanisms of interaction of these Gram negative bacteria with macrophages and potentially identify ways to increase bacterial killing.